LINGKUNGAN SEBAGAI FAKTOR PENUNJANG KEBERHASILAN PROSES PENDIDIKAN ISLAM - Khoirul Budi Utomo (Jurnal Keislaman, 2021)
The environment is everything that exists around humans, whether in the form of inanimate objects, living things or events that occur. including the conditions of society, especially those that can have a strong influence on individuals. The environment is where a person gets education directly or indirectly. Therefore the educational environment is material and social. and the educational environment is called the three Education Centers, namely family, school and community. In the educational process, especially Islamic education, it becomes an important supporting factor, because with a good contribution and a conducive environment, the best education will be created.